At home in diaspora : Black international writing - Walters, Wendy W. (Critical American studies series., 2005)
In At Home in Diaspora, Wendy W. Walters investigates the work of Chester Himes, Michelle Cliff, and other twentieth-century black international writers who have lived in and written from countries they do not call home. Walters suggests that in the absence of a recoverable land of origin, the idea of diaspora comes to represent a home that is not singular or exclusionary.